(untitled) (Journal of the College of Basic Education, 2022)
This research is a unique analytical reading to explore one of the structures that form the poetic experience of the rhythmic _in particular_ in poetry of the most famous poets of the gews known as(Samawal bin Aadiya) in the era of pre_Islam .It is a revealing illumination of the nature of the rhythmic tendency that fascinates the poet and poets of this class in general the researcher focused on the method of comprehensive statistic along the research area in order to prove the validity of the results and to avoid the impractical and improvisatory sentences that may disturb the evaluation of texts. The research is divided into two sections .The first is the outer frame of the structure(weights and rhymes) the second is to follow the internal structure of the rhythm as a tributary that distinguishes the poets in presenting their abilities through a number of art and method which is considered an enriching of the poetry music ، such as repetition of (alijaaz)on (alsodoor) ، (al_Tasree) ، (al_Tadweer)، alliteration and other genres، which did not occupy an area of search pages as (Al _Tarsee) for being rare.